The Effect Of Surface Disinfections Of Gutta-Percha On Shear Bond Strength Of Three Root Canal Sealers (Mustansiria Dental Journal, 2022)
Aim: The purpose was to study the influence of disinfectant solutions on shear bond strength between gutta percha (GP) and different sealers.Materials and method: 90 GP samples were used. Glassionemer sealer group A (n=20), mineral trioxide aggregate( MTA) sealer group B (n=20), iroot sealer group C (n=20), control group (n=10) for each group. Treated the surface of GP for each group by two disinfectant solutions (NaOCL 2.5%,  CHX 2%).Shear bond strength( S.B.S) test was calculate by digital universal testing machine.Results: iroot sealer (group C) with NaOCL solutions at (2.5%) increase shear bond which were significantly different P≤0.05 from CHX at (2%) and fresh control cones. glassionemer sealer (group A) gaive the lowest measured.Conclusions:  NaOCL solutions at 2.5% left a many pitting investigated on the GP surface. Thus it increased the bond with sealer. The quality of the surface texture and mechanical properties of GP were unaffected by a CHX solution of 2%. Therefore, they were considering as the safe disinfectant solutions for GP cones.